2022
DOI: 10.1177/0271678x221084410
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low frequency electromagnetic stimulation reduces ischemic stroke volume by improving cerebral collateral blood flow

Abstract: Extremely low frequency electromagnetic stimulation (ELF-EMS) has been considered as a neuroprotective therapy for ischemic stroke based on its capacity to induce nitric oxide (NO) signaling. Here, we examined whether ELF-EMS reduces ischemic stroke volume by stimulating cerebral collateral perfusion. Moreover, the pathway responsible for ELF-EMS-induced NO production was investigated. ELF-EMS diminished infarct growth following experimental stroke in collateral-rich C57BL/6 mice, but not in collateral-scarce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 82 publications
(137 reference statements)
1
7
0
Order By: Relevance
“…28 Previous preclinical studies have also shown that inhalation of NO, remote ischemic preconditioning, and extremely-low-frequency electromagnetic stimulation induced dilation of collaterals within the 24 hours after stroke and significantly reduced early ischemic damage. 5,29,30 We also found that H-BMSCs increased VEGF secretion and eNOS phosphorylation, leading to an early vasorelaxation before collateral remodeling.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…28 Previous preclinical studies have also shown that inhalation of NO, remote ischemic preconditioning, and extremely-low-frequency electromagnetic stimulation induced dilation of collaterals within the 24 hours after stroke and significantly reduced early ischemic damage. 5,29,30 We also found that H-BMSCs increased VEGF secretion and eNOS phosphorylation, leading to an early vasorelaxation before collateral remodeling.…”
Section: Discussionsupporting
confidence: 53%
“…3,4 Recent studies on collateral blood flow, including our own, highlight the promise of optimizing collateral circulation to improve outcomes in patients who have experienced an AIS. 5–7…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral ischemia/reperfusion was achieved by transient occlusion of both common carotid arteries. Animals were then either sham-exposed or treated with ELF-EMS (13.5 mT/60 Hz/20 min) for 4 consecutive days as previously established by our research group [ 13 , 14 ]. ELF-EMS significantly improved the neurological score of treated ischemic gerbils 3 days (8.0 ± 0.8 vs. 2.9 ± 0.9) and 7 days (7.67 ± 1.0 vs. 2.13 ± 1.0) after surgery ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
“…Our research group previously showed that in permanent stroke models, sinusoidal extremely low-frequency electromagnetic stimulation (ELF-EMS) reduced lesion size, improved neurological outcome, and enhanced cerebrovascular perfusion. It also increased eNOS activation in endothelial cells [ 13 , 14 ]. In reperfusion models, studies show a recovery of sensory motor functions [ 15 , 16 ], reduction in oxidative stress [ 17 ], and an effect on neuronal death and glia activation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%